Energy, exergy, thermoeconomic, exergoeconomic, and sustainability analyses of hydrogen-enriched diesel-biodiesel nano fuels - Bayramoglu, Kubilay; Polat, Fikret; Bayramoglu, Tolga; Saridemir, Suat; Agbulut, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This work intends to discuss the thermodynamic, economic, and sustainability analysis of hydrogen-enriched biodiesel-diesel and nanoparticle blends. In this direction, sunflower methyl ester (20 %) and diesel fuel (D100) are volumetrically blended (B20). Then, cerium oxide (CeO2) nanoparticles are added to B20 at a mass fraction of 100 ppm (B20CeO2). Furthermore, hydrogen of 5 lpm (B20CeO2H5) and 10 lpm (B20CeO2H10) is introduced into the combustion chamber from the intake manifold by mixing with the fresh air. The test engine is loaded from 15 to 60 Nm with increments of 15 Nm while it runs at a constant engine speed of 2000 rpm. The results show that the highest energy efficiencies are 28.9 % for B20CeO2H10 at 45 Nm. Besides, the highest exergy efficiencies are 27.01 % and B20CeO2H10 at 45 Nm. On the other hand, the best results are generally obtained for the B20CeO2H10 test fuel in terms of exergoeconomic and sustainability results. Crankshaft work has a particular work specific exergy cost of 138.9 US$/GJ for D100 and 184.6 $/GJ for B20CeO2H10. The sustainability index is determined as 1.37 for B20CeO2H10. In conclusion, these results reveal that adding nanoparticles and hydrogen considerably enhances the thermodynamic, economic, and sustainability metrics of the engine fuelled with diesel-biodiesel fuels.
Keywords: Hydrogen; Green energy; Thermodynamic; Nanofuels; Sustainability; COMBUSTION; PERFORMANCE; ENGINE; IMPROVEMENT; Chemistry; Electrochemistry; Energy & Fuels